Enhancing detection and characterization of lipids using charge manipulation in electrospray ionization-tandem mass spectrometry. (October 2020) - Randolph, Caitlin E.; Blanksby, Stephen J.; McLuckey, Scott A.
Graphical abstract: Highlights: Detection of subtle disturbances in lipid metabolism can provide key insights into many human pathologies. Modern electrospray ionization tandem mass spectrometry offers an unprecedented level of analytical power in lipid analysis. Manipulation of the nature and polarity of ionized lipids enhances detection and structural characterization. Contemporary solution- and gas-phase strategies to charge manipulation represent useful new tools for lipidomics. Abstract: Heightened awareness regarding the implication of disturbances in lipid metabolism with respect to prevalent human-related pathologies demands analytical techniques that provide unambiguous structural characterization and accurate quantitation of lipids in complex biological samples. The diversity in molecular structures of lipids along with their wide range of concentrations in biological matrices present formidable analytical challenges. Modern mass spectrometry (MS) offers an unprecedented level of analytical power in lipid analysis, as many advancements in the field of lipidomics have been facilitated through novel applications of and developments in electrospray ionization tandem mass spectrometry (ESI-MS/MS). ESI allows for the formation of intact lipid ions with little to no fragmentation and has become widely used in contemporary lipidomics experiments due to its sensitivity, reproducibility, and compatibility with condensed-phase modes of separation, such as liquid chromatography (LC). Owing to variations in lipid functional groups, ESI enables partial chemical separation of the lipidome, yet the preferred ion-type is not always formed, impacting lipid detection, characterization, and quantitation. Moreover, conventional ESI-MS/MS approaches often fail to expose diverse subtle structural features like the sites of unsaturation in fatty acyl constituents or acyl chain regiochemistry along the glycerol backbone, representing a significant challenge for ESI-MS/MS. To overcome these shortcomings, various charge manipulation strategies, including charge-switching, have been developed to transform ion-type and charge state, with aims of increasing sensitivity and selectivity of ESI-MS/MS approaches. Importantly, charge manipulation approaches afford enhanced ionization efficiency, improved mixture analysis performance, and access to informative fragmentation channels. Herein, we present a critical review of the current suite of solution-based and gas-phase strategies for the manipulation of lipid ion charge and type relevant to ESI-MS/MS.